A method for controlling the direction of the easy magnetization axis of garnet films by pulsed laser deposition
Through pulsed laser deposition technology, pulsed lasers with different single pulse energy and repetitive frequencies are used to hit the TbIG target, solving the problem of unstable regulation of the direction of the garnet thin film easily magnetization axis, and achieving stable regulation of the magnetic moment direction on the same substrate, reducing costs and improving flexibility.
Patent Information
- Application Number
- CN202310325158.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-03-30
AI Technical Summary
When the prior art regulates the axial direction of the garnet film, the magnetic moment direction is unstable due to the limitations of the substrate type, crystal phase and film thickness.
Through pulsed laser deposition technology, pulsed lasers with different single pulse energy and repetitive frequencies are used to strike the TbIG target, and garnet films are prepared, and their magnetization axis direction can be adjusted in or out of the plane.
It is realized that on the same substrate, by adjusting the process parameters of the pulsed laser, the magnetic moment direction of the garnet film is stably adjusted, reducing experimental costs and improving flexibility.
Smart Images

Figure CN116356261B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic thin film materials, and in particular relates to a method for regulating the direction of the easy magnetization axis of a garnet film by pulsed laser deposition. Background Art
[0002] High-quality garnet films play an important role in promoting the development of spin electronics research. 12 , YIG) and thulium iron garnet (Tm3Fe5O 12 , TmIG) are very ideal ferrimagnetic insulator materials with very low Gilbert damping factors and very large spin wave propagation lengths. The easy magnetization axis of YIG is usually located in the film plane, and its prospects in the spin Seebeck effect and microwave fields have been widely studied; while the easy magnetization axis of TmIG is usually located outside the film plane, with perpendicular magnetic anisotropy, and has great potential in the fields of spin-orbit moment, topological Hall effect, and chiral magnetic structure. It can be seen that the orientation of the magnetic moment of garnet film affects its application in different fields.
[0003] The conventional method to change the direction of the easy magnetization axis of garnet film is to select single crystal substrates with different lattice constants or crystal plane orientations through magnetoelastic coupling, and to adjust the direction of its magnetic moment by forming in-plane compressive stress or tensile stress between the substrate and the garnet film deposited thereon. However, as the type or crystal phase of the substrate changes, the growth process also changes accordingly. In addition, as the thickness of the garnet film increases, the stress from the substrate gradually relaxes, resulting in instability in the film structure and magnetic moment direction. Therefore, this method is affected by many different experimental conditions and restricted by the thickness of the film. Summary of the invention
[0004] The object of the present invention is to provide a method for regulating the direction of the easy magnetization axis of a garnet film by pulsed laser deposition, characterized in that the method comprises the following steps:
[0005] S1: Place the cleaned substrate in the chamber of the pulsed laser deposition equipment, evacuate the chamber, set the chamber parameters, and strike the TbIG target with a pulsed laser. The repetition frequency of the pulsed laser is 1-8 Hz.
[0006] S2: After the laser striking is completed, the temperature in the cavity is naturally reduced to room temperature, and then the TbIG film is taken out and obtained;
[0007] The easy magnetization axis of the garnet film in S2 prepared by setting the single pulse energy of the pulse laser to 200-340 mJ, the average power to 40-75 mW and the voltage to 18.5-22 kV is located in the plane; the easy magnetization axis of the garnet film in S2 prepared by setting the single pulse energy of the pulse laser to 350-500 mJ, the average power to 75-110 mW and the voltage to 22-25.5 kV is located out of the plane.
[0008] Furthermore, in S1, the substrate is scandium-doped gadolinium gallium garnet, and the crystal phase of the substrate is (001).
[0009] Furthermore, in S1, the parameters in the chamber are: when the vacuum is evacuated to a vacuum degree of 2.0×10-6 Pa and the temperature of the substrate in the chamber rises to 750°C, oxygen is introduced and the oxygen pressure is maintained at 1.0-5.0 Pa.
[0010] Furthermore, when the easy magnetic axis of the prepared garnet film is located in the plane, the deposition rate of the TbIG film is 0.28 Å / s; when the easy magnetic axis of the prepared garnet film is located out of the plane, the deposition rate of the TbIG film is 0.36 Å / s.
[0011] Furthermore, the repetition frequency of the pulsed laser is 3-5 Hz.
[0012] Furthermore, in S2, the thickness of the two TbIG films obtained is 2-200 nm.
[0013] Furthermore, when the single pulse energy is set to 300 mJ, the easy magnetization axis of the prepared garnet film is located in the plane; when the single pulse energy is set to 400 mJ, the easy magnetization axis of the prepared garnet film is located out of the plane, and the thickness of the two TbIG films prepared is 50 nm.
[0014] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:
[0015] 1. The present invention uses the same substrate to ensure that the lattice mismatch between the film and the substrate is theoretically the same. The direction of the film magnetic moment can be regulated by only changing the single pulse energy intensity of the pulsed laser in the preparation process.
[0016] 2. The present invention can deposit TbIG thin films with any thickness in the range of nanometer to submicron scale, and can control the direction of its magnetic moment, with strong stability.
[0017] 3. The present invention not only controls a single variable, is simple and easy to implement, but also greatly reduces the experimental cost, while also improving the flexibility of the experiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1Schematic diagram of the structure of GSGG (substrate, crystal orientation 0 0 1) / TbIG (thin film) in the present invention.
[0019] Figure 2 Schematic diagram of XRD spectrum of three samples (I) in which the single pulse energy of the laser in Examples 1-3 of the present invention is in the range of 200-340 mJ.
[0020] Figure 3 Schematic diagram of XRD spectrum of three samples (II) in Examples 1-3 of the present invention with single pulse energy of the laser in the range of 350-500 mJ.
[0021] Figure 4 It is the X-ray diffraction (XRD) spectrum of GSGG (substrate, crystal orientation 0 0 1) / TbIG (thin film) in the present invention.
[0022] Figure 5 Schematic diagram of inverse spatial mapping of GSGG (substrate, crystal orientation 0 0 1) / TbIG (thin film) at room temperature in the present invention.
[0023] Figure 6 Schematic diagram of the hysteresis loop of GSGG (substrate, crystal orientation 0 0 1) / TbIG (thin film) at room temperature in the present invention.
[0024] Figure 7 Schematic diagram of the Hall loop of GSGG (substrate, crystal orientation 0 0 1) / TbIG / Pt at room temperature
[0025] Figure 8 Schematic diagram of the spin Seebeck voltage-magnetic field loop of GSGG (substrate, crystal orientation 0 0 1) / TbIG / Pt at room temperature DETAILED DESCRIPTION
[0026] A method for regulating the direction of the easy magnetization axis of a garnet film by pulsed laser deposition according to the present invention will be described in more detail below in conjunction with a schematic diagram, wherein a preferred embodiment of the present invention is shown. It should be understood that those skilled in the art can modify the present invention described herein while still achieving the advantageous effects of the present invention. Therefore, the following description should be understood as being widely known to those skilled in the art and not as a limitation to the present invention.
[0027] like Figure 1 As shown, the present invention uses a computer-controlled pulsed laser deposition device PLD to deposit scandium-doped gadolinium gallium garnet (Gd3Sc2Ga3O 12 The single crystal with the crystal phase of (0 0 1) as the substrate was used to prepare the samples of GSGG / TbIG (Ⅰ) and GSGG / TbIG (Ⅱ). The specific steps are as follows:
[0028] Place the cleaned substrate into the PLD chamber of the pulsed laser deposition equipment and evacuate the chamber until the background vacuum drops to 2.0×10 -6 Pa, the temperature in the cavity is raised to 750 ° C, oxygen is passed, and the oxygen pressure is maintained at 1.0-5.0 Pa; the TbIG target is struck by a pulsed laser, the single pulse energy of the laser is 200-340 mJ, the average power is 40-75 mW, the voltage is 18.5-22 kV, and the laser repetition frequency is 1-8 Hz. After the laser striking is completed, a terbium iron garnet film with a thickness of 2-200 nm is formed, and the sample (Ⅰ) is taken out after the temperature in the cavity naturally drops to room temperature.
[0029] Place the cleaned substrate into the PLD chamber of the pulsed laser deposition equipment and evacuate the chamber until the background vacuum drops to 2.0×10 -6 Pa, the temperature in the cavity is raised to 750 ° C, oxygen is passed, and the oxygen pressure is maintained at 1.0-5.0 Pa; the TbIG target is struck by a pulsed laser, the single pulse energy of the laser is 350-500 mJ, the average power is 75-110 mW, the voltage is 22-25.5 kV, and the laser repetition frequency is 1-8 Hz. After the laser striking is completed, a terbium iron garnet film with a thickness of 2-200 nm is formed, and the sample is taken out after the temperature in the cavity naturally drops to room temperature (II).
[0030] Example 1: Preparation of the first group of samples I and II
[0031] The cleaned substrate GSGG (0 0 1) was placed in the pulsed laser deposition equipment PLD chamber and evacuated until the background vacuum of the chamber dropped to 2.0×10 -6 Pa, the temperature in the cavity is raised to 750 ℃, oxygen is passed, and the oxygen pressure is maintained at 1.0-5.0Pa; the TbIG target is struck by a pulsed laser, the single pulse energy of the laser is 200 mJ, the average power is 40 mW, the voltage is 18.5 kV, and the laser repetition frequency is 1 Hz. After the laser striking is completed, a terbium iron garnet film with a thickness of about 2 nm is formed, and the sample (Ⅰ) is taken out after the temperature in the cavity naturally drops to room temperature.
[0032] The cleaned substrate GSGG (0 0 1) was placed in the pulsed laser deposition equipment PLD chamber and evacuated until the background vacuum of the chamber dropped to 2.0×10 -6 Pa, the temperature in the cavity is raised to 750 ℃, oxygen is passed, and the oxygen pressure is maintained at 1.0-5.0Pa; the TbIG target is struck by a pulsed laser, the single pulse energy of the laser is 350 mJ, the average power is 75 mW, the voltage is 22kV, and the laser repetition frequency is 1Hz. After the laser striking is completed, a terbium iron garnet film with a thickness of about 2 nm is formed, and the sample (II) is taken out after the temperature in the cavity naturally drops to room temperature.
[0033] Example 2: Preparation of the second group of samples I and II
[0034] Place the cleaned substrate into the PLD chamber of the pulsed laser deposition equipment and evacuate the chamber until the background vacuum drops to 2.0×10 -6 Pa, the temperature in the cavity was raised to 750 ℃, oxygen was passed, and the oxygen pressure was maintained at 1.0-5.0 Pa; the TbIG target was struck by a pulsed laser, the single pulse energy of the laser was 340 mJ, the average power was 70 mW, the voltage was 21.5 kV, and the laser repetition frequency was 8 Hz. After the laser striking was completed, a terbium iron garnet film with a thickness of 200 nm was formed, and the sample was taken out after the temperature in the cavity naturally dropped to room temperature (Ⅰ).
[0035] Place the cleaned substrate into the PLD chamber of the pulsed laser deposition equipment and evacuate the chamber until the background vacuum drops to 2.0×10 -6 Pa, the temperature in the cavity was raised to 750 ° C, oxygen was introduced, and the oxygen pressure was maintained at 1.0-5.0 Pa; the TbIG target was struck by a pulsed laser, the single pulse energy of the laser was 500 mJ, the average power was 110 mW, the voltage was 25.5 kV, and the laser repetition frequency was 8 Hz. After the laser striking was completed, a terbium iron garnet film with a thickness of 200 nm was formed, and the sample was taken out after the temperature in the cavity naturally dropped to room temperature (II).
[0036] Example 3: Preparation of preferred sample groups I and II
[0037] Place the cleaned substrate into the PLD chamber of the pulsed laser deposition equipment and evacuate the chamber until the background vacuum drops to 2.0×10 -6 Pa, the temperature in the cavity was raised to 750 ° C, oxygen was introduced, and the oxygen pressure was maintained at 1.0-5.0 Pa; the TbIG target was struck by a pulsed laser, the single pulse energy of the laser was 300 mJ, the average power was 65 mW, the voltage was 20.5 kV, and the laser repetition frequency was 4 Hz. After the laser striking was completed, a terbium iron garnet film with a thickness of 100 nm was formed, and the sample was taken out after the temperature in the cavity naturally dropped to room temperature (Ⅰ).
[0038] Place the cleaned substrate into the PLD chamber of the pulsed laser deposition equipment and evacuate the chamber until the background vacuum drops to 2.0×10 -6Pa, the temperature in the cavity was raised to 750 ° C, oxygen was introduced, and the oxygen pressure was maintained at 1.0-5.0 Pa; the TbIG target was struck by a pulsed laser, the single pulse energy of the laser was 400 mJ, the average power was 83 mW, the voltage was 24.5 kV, and the laser repetition frequency was 4 Hz. After the laser striking was completed, a terbium iron garnet film with a thickness of 100 nm was formed, and the sample was taken out after the temperature in the cavity naturally dropped to room temperature (II).
[0039] Example 4
[0040] XRD patterns of three samples (I) with single pulse energy of the laser in the range of 200-340 mJ were tested, and the following results were obtained: Figure 2 The XRD spectrum diagram shown in FIG. 1 and the XRD spectrum test of three samples (II) with single pulse energy of the laser in the range of 350-500 mJ, obtained as follows Figure 3 The schematic diagram of the XRD spectrum shown in the figure shows that, based on the peak position, peak intensity and area of the characteristic peaks of the (Ⅰ) and (Ⅱ) series of TbIG samples in the XRD spectrum of the above two intervals, it can be concluded that the samples deposited under 300 and 400 mJ conditions are the optimal samples in the corresponding intervals.
[0041] Example 5: Property test analysis of preferred sample groups (I) and (II)
[0042] The prepared GSGG(0 0 1) / TbIG samples (I) and (II) were placed in an X-ray diffractometer for phase testing to obtain XRD spectra. Figure 4 As shown, it can be seen that samples (Ⅰ) and (Ⅱ) have a series of diffraction peaks such as (0 0 4), (0 0 8), and (0 0 12) with the substrate GSGG (0 0 1), showing good single crystallinity; under the same substrate (crystal phase), the XRD diffraction peaks of samples (Ⅰ) and (Ⅱ) are located on the left and right of the corresponding substrate diffraction peaks, respectively, indicating that the crystal constants of TbIG thin film samples (Ⅰ) and (Ⅱ) prepared by pulsed laser at different single pulse energy intensities are different.
[0043] The inverse spatial mapping images of samples (I) and (II) were analyzed by XRD, as shown in the attached figure. Figure 5 As shown, it can be seen that the peak of type I TbIG is on the left side of the substrate GSGG peak, while the peak of type II TbIG is on the right side of the substrate GSGG peak, indicating that the lattice sizes of the two configurations of TbIG are different, which more directly proves the reliability of the XRD results.
[0044] The prepared GSGG (0 0 1) / TbIG samples (I) and (II) were placed in a vibrating sample magnetometer, and magnetic measurements were performed in the directions parallel (in-plane, IP) and perpendicular (out-of-plane, OOP) to the film plane to obtain hysteresis loops. Figure 6 As shown in (Ⅰ), the easy axis is in-plane (IP, solid line) and the hard axis is out-plane (OOP, hollow sphere curve). It can be obtained that the coercive fields in the hard and easy axis directions are about 1500 Oe and 10 Oe, respectively, and the saturation magnetization intensity is basically the same, about 45emu / cm 3 , which corresponds to Figure 1 The (Ⅰ) configuration TbIG sample in the attached Figure 6 As shown in (Ⅱ), the easy magnetization axis is out of plane (OOP, square curve) and the hard axis is in plane (IP, hollow sphere curve). It can be obtained that the coercive fields in the hard and easy axis directions are about 1500 Oe and 20 Oe, respectively, and the saturation magnetization intensity is basically the same, about 45 emu / cm 3 , which corresponds to Figure 1 The magnetic measurement results show that the pulsed laser in the present invention can prepare TbIG films with in-plane (I) and perpendicular (II) magnetic anisotropy under different single pulse energy intensities, and the saturation magnetization intensities of (I) and (II) samples are basically the same; the present invention not only controls a single variable, is simple and easy to implement, but also greatly reduces the experimental cost and improves the flexibility of the experiment.
[0045] Then, samples (I) and (II) were put into magnetron sputtering, and a platinum layer with the same process and the same thickness (3 nm) was deposited on the TbIG surface to prepare a TbIG / Pt heterojunction. The anomalous Hall effect (magnetic field applied outside the film surface) and the spin Seebeck effect (magnetic field applied inside the film surface) were measured at room temperature. The accuracy of the magnetic measurement was verified by the measurement results of electrical and thermal transport.
[0046] The Hall loops of type I and II TbIG / Pt heterojunctions were measured in a transport measurement system at room temperature with a magnetic field applied out of the plane of the film sample. Figure 7 As shown in (Ⅰ), the Hall loop of TbIG / Pt is saturated under a magnetic field of 1500 Oe. The shape of the loop near zero field is similar to that of YIG / Pt. In general, YIG has in-plane magnetic anisotropy, which proves that TbIG also has in-plane magnetic anisotropy, that is, the direction of the easy magnetization axis is in the plane. Figure 7 As shown in (Ⅱ), the Hall loop of TbIG / Pt can be saturated near zero field, and the shape of the loop shows a sharp jump, proving that the easy magnetization axis of TbIG is out of the plane at this time.
[0047] The spin Seebeck voltage-magnetic field loops of type I and II TbIG / Pt heterojunctions were measured in a transport measurement system at room temperature, with the magnetic field applied in the plane of the thin film sample. Figure 8As shown in (Ⅰ), the spin Seebeck voltage-magnetic field loop of TbIG / Pt can be saturated under zero field, and the shape of the loop shows a sharp jump, which proves that the easy magnetization axis of TbIG is in the plane at this time; as shown in the attached Figure 8 As shown in (Ⅱ), the spin Seebeck voltage-magnetic field loop of TbIG / Pt is saturated under a magnetic field of 1500 Oe, proving that the easy magnetization axis of TbIG is out-of-plane at this time.
[0048] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any technician in the relevant technical field, without departing from the scope of the technical solution of the present invention, makes any form of equivalent replacement or modification to the technical solution and technical content disclosed in the present invention, which does not depart from the content of the technical solution of the present invention and still falls within the protection scope of the present invention.
Claims
1. A method for regulating the direction of the easy magnetization axis of a garnet film by pulsed laser deposition, characterized in that: The steps include: S1: Place the cleaned substrate in the chamber of the pulsed laser deposition equipment, evacuate the chamber, set the chamber parameters, and strike the TbIG target with a pulsed laser. The repetition frequency of the pulsed laser is 1-8 Hz. S2: After the laser striking is completed, the temperature in the cavity is naturally reduced to room temperature, and then the TbIG film is taken out and obtained; The easy magnetization axis of the garnet film in S2 prepared by setting the single pulse energy of the pulsed laser to 200-340 mJ, the average power to 40-75 mW and the voltage to 18.5-22 kV is located in the plane; the easy magnetization axis of the garnet film in S2 prepared by setting the single pulse energy of the pulsed laser to 350-500 mJ, the average power to 75-110 mW and the voltage to 22-25.5 kV is located out of the plane; In S1, the chamber parameters are: evacuate to a vacuum degree of 2.0×10 -6 Pa. When the temperature of the substrate in the cavity rises to 750℃, oxygen is introduced and the oxygen pressure is maintained at 1.0-5.0 Pa.
2. The method for controlling the direction of the easy magnetization axis of a garnet film by pulsed laser deposition according to claim 1, characterized in that: In S1, the substrate is scandium-doped gadolinium gallium garnet, and the crystal phase of the substrate is (001).
3. The method for controlling the direction of the easy magnetization axis of a garnet film by pulsed laser deposition according to claim 1, characterized in that: When the easy magnetic axis of the prepared garnet film is located in the plane, the deposition rate of the TbIG film is 0.28 Å / s; when the easy magnetic axis of the prepared garnet film is located out of the plane, the deposition rate of the TbIG film is 0.36 Å / s.
4. The method for controlling the direction of the easy magnetization axis of a garnet film by pulsed laser deposition according to claim 1, characterized in that: The repetition frequency of the pulse laser is 3-5 Hz.
5. The method for controlling the direction of the easy magnetization axis of a garnet film by pulsed laser deposition according to claim 1, characterized in that: In S2, the thickness of the two TbIG films prepared is both 2-200 nm.
6. The method for controlling the direction of the easy magnetization axis of a garnet film by pulsed laser deposition according to claim 5, characterized in that: When the single pulse energy is set to 300 mJ, the easy magnetization axis of the prepared garnet film is located in the plane; when the single pulse energy is set to 400 mJ, the easy magnetization axis of the prepared garnet film is located out of the plane, and the thickness of the two prepared TbIG films is 50 nm.
Citation Information
Patent Citations
Magnetic dual-layer garnet material with in-plane and out-plane easily magnetized directions, and preparation method thereof
CN108389718A